Plastic Waste (In)Visibility in Plasticity - Ogutveren, Neylan Aular (Tahiti, 2025)
This article examines the video game Plasticity as a compelling narrative medium that represents and critiques the ecological ramifications of plastic consumption in the Anthropocene era. The game’s dystopian setting, where players navigate through environments devastated by plastic waste, serves as a metaphor for the real-world issues of waste management and environmental neglect. By integrating theories from material ecocriticism and close gaming methodologies, this paper analyses Plasticity both as a piece of eco-fiction and as an interactive experience that challenges players to reflect on their own consumption habits. The game’s design and player agency are highlighted as tools that expose the often invisible conse- quences of waste disposal practices. I argue that Plasticity utilizes the concept of Chthulucene aesthetics, which I define as an approach that embraces ecological entanglement and multispecies perspectives, challenging traditional views of beauty by finding harmony in environmental disturbances and the interconnectedness of all life forms, to illuminate the strategic invisibility of plastic waste. The analysis reveals the game’s potential to open a space for interpretation of what remains in the dark by practices dictated as normal in terms of plastic waste disposal practices in the Anthropocene.